A ground reaction force model of speed skating based on non-contact measurement system - Zhu, Q.; Yang, C.; Ke, P.; Yang, H.; Hong, P. (iScience, 2024)
Accurate collection and analysis of ground reaction force (GRF) data are crucial for optimizing the tech nical movements of speed skaters; however, it has been a challenge for the limitations of experimental equipment and application scenarios. Therefore, we proposed a novel approach for estimating GRF based on kinematics obtained from markerless video tracking systems and achieved low errors compared with the experimental data. Our method allows for further biomechanical analysis, including muscle force and power, during speed skating competitions.